PENGARUH PEMBERIAN PAKAN BUATAN DARI KOMBINASI TEPUNG CACING TANAH (Lumbricus rubellus) DAN TEPUNG DAUN PEPAYA TERHADAP PERTUMBUHAN IKAN NILA (Oreochromis niloticus) - Rukisah, Rukisah; Simanjuntak, Ricky Febrinaldy; Anugrah, Wulan (Jurnal Harpodon Borneo, 2021)
The problem that often arises in tilapia cultivation is the low growth of fish caused by the provision of feed that contains high energy but cannot be digested by fish. Utilization of commercial feed as feed for tilapia growth is less effective because the feed is still complex so it requires energy to be broken down into more simple. The method used in this study was a completely randomized design (CRD) which was then analyzed using one way ANOVA variance. The best results were obtained in treatment 4 with an absolute weight value of 2.97, absolute length of 1.19, specific growth rate of 2.75, survival of 83.33% and feed conversion of 0.95%. The conclusion of this study is the treatment of 4 absolute weight of 2.97 g and absolute length of 1.19 cm.